RESEARCHER’S ATTITUDE TOWARDS SCIENTIFIC ACTIVITY WITHIN THE CONTEXT OF VUCA ENVIRONMENTS. : CASE: DEPARTMENT OF NATURAL SCIENCES CORE LUZ COL - González, Omar; González, María; Salgado, Nelitza (Revista Arbitrada Formación Gerencial, 2024)
The objective of the research was to analyze the attitude towards the scientific activity of the research professor of the Department of Natural Sciences of the LUZ COL Nucleus, under the VUCA environments. It was an analytical type of research, under a field design, through a case study, in the same way the population was also made up of 18 teachers from the Department of Natural Sciences, a questionnaire with 21 questions was applied. The results show that there is a degree of highly direct correspondence between the investigative attitude and the VUCA environments. It is concluded that the investigative attitude should be strengthened by reinventing and adapting to the new reality demanded by the complexity of the processes and turning them into a strength to open new horizons in research under positive transformations and adaptability.